Physicochemical, microbiological and microscopic evaluation of artisanal rapaduras produced in Cuiabá, Mato Grosso, Brazil - Braun, Carla Luciane Kreutz; Oliveira, Adriana Paiva de; Pedro, Francisca Graciele Gomes; Arruda, Gevanil Lene; Lima, Marcio Gonçalo de; Villa, Ricardo Dalla (Acta Scientiarum. Technology, 2016)
The aim of this work was the physicochemical, microbiological and microscopic evaluation of artisanal rapaduras produced in Cuiabá, Mato Grosso State, Brazil. The determination of the proximal composition, pH and the microscopic analyses were made according to the Association of Official Analytical Chemists (AOAC). The concentrations of minerals and toxic metals were quantified by flame atomic absorption spectrometry. The Coliforms at 45Â°C and Salmonella sp. were determined according to the American Public Health Association (APHA). The results obtained were: moisture (6.09 to 16.34%), ash (0.07 to 1.88%), insoluble solids (0.11 to 11.3%), pH (4.73 to 5.61), proteins (0.21 to 0.47%), sucrose (13.15 to 43.89%), and reducing sugars (10.96 to 26.28%). Significant differences were found between the samples (p Â£ 0.05) as well as nonconformities in relation to national regulations. The mineral contents showed significant differences between lots of samples (p Â£ 0.05) and some lots presented Cd and Pb concentrations above the maximum values allowed by Brazilian legislation. High quantities of unwanted materials were detected and none of the samples presented microbiological contamination. The results suggest the creation of technical standards for quality control for the production of rapaduras to ensure food safety. Â